The Role of Service Quality, Trust and Location in Increasing Café Customer Repurchase Intention - Arie Setyawan; Alfian Perdana Putra; Dwi Aprilia Nurhaliza; Gustiani Gustiani; Muhammad Mandalla Faradis; Nurul Qomariah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2023)
Café is a place to discuss something with a relaxed atmosphere which is currently favored by all groups. Light snacks and drinks are always served in a relaxed atmosphere. The purpose of writing this research is to determine the impact of service quality, consumer trust, and location on repurchasing intentions at Cafe Senja Jember. The number of samples in this study amounted to 100 customers Café Senja Jember. The basis for this sampling is that a regional study can be conducted if the sample ranges from 50 to 100 respondents. Description analysis, reliability test and validity test as well as multiple linear regression analysis were used in this study. The results of the research after using multiple linear regression analysis showed that partially the variables of service quality, consumer trust, and location have a positive influence on the variable of repurchase intention at Cafe Senja Jember. The dominance test shows that the value of the service quality variable is greater than the other variables. The coefficient of determination or R square shows a value of 0.829. This shows that all independent variables (service quality, consumer trust, and location) have a contribution of 82.9% to the dependent variable (consumer repurchase intention) at Café Senja Jember.